Quasi-Lagrangian energetics of an intense Mediterranean cyclone - Michaelides, S.C.; Prezerakos, N.G.; H. A. Flocas (Quarterly Journal of the Royal Meteorological Society, 1999)
Studies of the energetics of synoptic-scale systems and similar kinds of investigation have traditionally used a Eulerian framework. In this study, the energetics of a synoptic-scale system have been considered using a quasi-Lagrangian method, in order to isolate the disturbance under consideration within a volume which moves together with the system at each stage of its development. Applying a Lagrangian framework implies that the dimensions of the computational area can be framework on the basis of predetermined criteria. In this study, an area surrounding a depression as shown on the surface analysis, has been selected. This area moves together with the centre of the depression. The energetics results obtained using such a quasi-Lagrangian scheme are compared to those obtained by using a Eularian framework. The synoptic-scale system studied here is a wintertime frontal depression, the greatest development of which occurred in the central Mediterranean on 7 December 1991. This depression moved east accompanied by significant temperature changes, heavy precipitation and gale force winds.
cited By (since 1996)6
Keywords: atmospheric dynamics; cyclone; energetics; kinetic energy; Lagrangian analysis; Mediterranean Sea; potential energy; Synoptic meteorology